2007
DOI: 10.1128/aem.02426-06
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Pseudomonas sp. Strain 7-6 to Quaternary Ammonium Compounds and Their Degradation via Dual Pathways

Abstract: Pseudomonas sp. strain 7-6, isolated from active sludge obtained from a wastewater facility, utilized a quaternary ammonium surfactant, n-dodecyltrimethylammonium chloride (DTAC), as its sole carbon, nitrogen, and energy source. When initially grown in the presence of 10 mM DTAC medium, the isolate was unable to degrade DTAC. The strain was cultivated in gradually increasing concentrations of the surfactant until continuous exposure led to high tolerance and biodegradation of the compound. Based on the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 17 publications
2
50
0
1
Order By: Relevance
“…A previous study conducted in Ria de Aveiro showed that Pseudomonads represent 34.5% of the culturable fraction of naphthalene-degrading bacterioneuston of the SML of the Ria de Aveiro [14]. This group is also reported as tolerant to high concentrations of anionic [35] and cationic surfactants [66] and as an efficient biosurfactant producer [9]. The present study demonstrates a high representation (64%) of this genus in the culturable fraction of the surfactant-resistant bacterioneuston and confirms the relevance of Pseudomonads in the particular environment of the estuarine SML.…”
Section: Pseudomonads Among Surfactant-resistant Bacterioneuston Isolmentioning
confidence: 99%
“…A previous study conducted in Ria de Aveiro showed that Pseudomonads represent 34.5% of the culturable fraction of naphthalene-degrading bacterioneuston of the SML of the Ria de Aveiro [14]. This group is also reported as tolerant to high concentrations of anionic [35] and cationic surfactants [66] and as an efficient biosurfactant producer [9]. The present study demonstrates a high representation (64%) of this genus in the culturable fraction of the surfactant-resistant bacterioneuston and confirms the relevance of Pseudomonads in the particular environment of the estuarine SML.…”
Section: Pseudomonads Among Surfactant-resistant Bacterioneuston Isolmentioning
confidence: 99%
“…Existem trĂȘs proteĂ­nas responsĂĄveis pelo mecanismo: uma proteĂ­na de membrana externa que atua como um canal durante o transporte, uma proteĂ­na da membrana interna que traduz energia eletroquĂ­mica de prĂłtons em vetor de deslocamento dos compostos transportados e um componente periplĂĄsmico de transição, que liga as proteĂ­nas da membrana interna e externa (Pietras et al 2008). Sabe-se que a resistĂȘncia a compostos Ă  base de amĂŽnia quaternĂĄria em E. coli estĂĄ ligada Ă  superexpressĂŁo de proteĂ­nas de transporte, ocorrendo assim intenso eϐluxo de substĂąncias atravĂ©s da membrana celular (Shahcheraghi et al 2007, Takenaka et al 2007.…”
Section: Introductionunclassified
“…7 Of the different novel strategic designs, surfaces capable of releasing antibiotics have shown to display effective bactericidal properties; however these have been shown to possess a number of disadvantages including long leaching times, lack of control of concentration upon delivery, and poor durability. [8][9][10][11][12] Consequently, an approach driven by a mechanism that is independent from existing conventional methods is of high importance, especially one based on the material's inherent properties, which would push new frontiers in antibacterial surface design. Hence, much attention has shifted to what the natural world has to offer by reverse-engineering bio-inspired antibacterial surface solutions.…”
Section: Introductionmentioning
confidence: 99%